Effects of Low/Medium-Intensity Exercise on Fat Metabolism after a 6-h Fast - Liu, Ming-Yi; Chen, Shung-Quan (International journal of environmental research and public health, 2022)
The effects of fasting and different exercise intensities on lipid metabolism were investigated in 12 male students aged 19.9 ± 1.4 years, with maximal oxygen consumption (VO2max) of 50.33 ± 4.0 mL/kg/min, using a counterbalanced design. Each participant ran on a treadmill at 45% and 65% VO2max continuously for 20 min, followed by running at 85% VO2max for 20 min (or until exhaustion) under a fed or fasted state (6 h). The respiratory exchange ratio (RER), blood glucose (BGLU), blood lactate (BLA), and blood triglyceride (TG) were analyzed during exercise. The results showed that the intensity of exercise did not significantly affect the BGLU and TG in the fed state. The levels of both RER and BLA increased as the intensity of exercise increased from low to high (45, 65, and 85% VO2max), and more energy was converted from fat into glucose at a high intensity of exercise. In the fasted state of 6 h, the BGLU level increased parallel to the intensity of exercise. The RER was close to 1.0 at a high intensity of exercise, indicating that more energy was converted from glycogen. At the intensities of 45 and 65% VO2max, the RER and concentration of TG were both lower in the fasted than in the fed state, showing that a higher percentage of energy comes from fat than in the fed state at 45 and 65% VO2max. When running at 85% VO2max, the BGLU concentration was higher in the fasted than in the fed state, indicating that the liver tissues release more BGLU for energy in the fasted state. Therefore, in the fasted state, running at 45% and 65% of VO2max significantly affects lipid metabolism. On the contrary, the higher RER and BGLU concentrations when running at 85% VO2max revealed no significant difference between the two probes. This study suggests that medium- and low-intensity exercise (45 and 65% VO2max) in the fasted state enhances lipid metabolism.